Isolation and identification of casual disease of eucalyptus pellita - Muhammad Safril, Abdul Rahim (Universiti Malaysia Sarawak (UNIMAS), 2012)
Eucalyptus plantation in Malaysia is still new and need a lot of attention and care especially on the prevention against the disease infection. Disease infection in the timber tree species of the Eucalyptus pellita negatively impacts the timber yield throughout the world and affecting the production. A study was conducted in Sempadi Forest Plantation in Bau area, the tissues from the Eucalyptus pel/ita were collected, the disease de cription were made based on the symptoms, and the pathogen were isolated from the leaves and identified for their species based on the morphology and the molecular approach. The common disease symptoms were brown leaf spots, yellow leaf spots, reddish brown leaf spots, yellowish spots, whitish grey spots and also some discolouration of the leaf tips. The fungi isolated were Cladosporium sp., Pestalotiopsis sp., Aspergillus niger, Aspergillus jlavus, Trichoderma sp., Botryodiplodia theobromae and Guignardia sp. Three physiological tests were conducted on the fungi isolated which were on different artificial media, temperature and pH. Three different media were used in the tests which were the MEA, CMA, and PDA. There were significant differences on the average growth of the fungi and the MEA was the best media for BOlryodiplodia theobromae and Trichoderma sp. while PDA was the best for Pestalotiopsis sp. The tested temperature was at 15, 20, 25, 30, 35, 40"C. The fungi isolated grew the best at the moderate temperature which was in the range of 25-30"C. The pH test were conducted with the tested pH were at pH 3,4,5,6,7,8 and the pH did not have a significant impact to the growth for most of the fungi. Pathogenicity test has been carried out on the detached leaf of the E. pellita by infecting it with Cladosporium sp. A serious study on the planted forest disease in Malaysia should be carried out on the wide range of timber species as a proper documentation on pathogen will resulting in the good prevention measures.